Industrial cybersecurity efficiently secure critical infrastructure systems - Ackerman, Pascal (Packt Publishing, 2017)
Learn about endpoint protection such as anti-malware implementation, updating, monitoring, and sanitizing user workloads and mobile devices. Filled with practical examples to help you secure critical infrastructure systems efficiently. A step-by-step guide that will teach you the techniques and methodologies of building robust infrastructure systems. Industrial cybersecurity begins by introducing Industrial Control System (ICS) technology, including ICS architectures, communication media, and protocols.